Peran Hyaluronic Acid untuk Skin Rejuvenation - Triastuti, Nenny; Srihartati, Enik; Primadina, Nova; Nabila, Iffah (JurnalMU: Jurnal Medis Umum, 2024)
Background: As you get older, some cells in the body experience a decrease in the amount of production, including hyaluronic acid. Hyaluronan or hyaluronic acid (HA) is a molecule involved in skin moisture. Skin that loses moisture easily becomes dehydrated and signs of aging appear. Moreover, extrinsic factors such as exposure to UV rays and changing weather conditions also affect the condition of the skin and cause damage to the skin's protective layer. Objective: to determine the role and effectiveness of hyaluronic acid for skin rejuvenation. Methods: Literature review with the title “The Role of Hyaluronic Acid for Skin Rejuvenation” is gain by systematic reviewing of some original research article journal and literature review using search engines such as Google Scholar, PubMed, Scopus, and Elsevier. Results: Hyaluronic Acid (HA) has a role in regulating various biological processes such as skin repair, wound healing, anti-inflammatory, tissue regeneration, and immunomodulation. HA filler injection is an effective therapy for skin rejuvenation because it hydrates, removes fine lines and signs of aging on the skin, and is used to shape facial anatomy according to the patient's wishes. Conclusion : Hyaluronic acid is proven to have effectiveness on skin rejuvenation.